Pengaruh Motivasi, Kepuasan Kerja dan Stress Kerja Terhadap Kinerja Karyawan pada PT. Agung Automall Bengkulu - Nopran Syaputra; Merta Kusuma (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to know the effect of motivation, job satisfaction and job stress on employee performance at PT. Agung Automall Bengkulu either partially or simultaneously. There are several factors discussed in this study includesthe motivation, job satisfaction and job stress. The objects in this study are 105 employees of PT. Agung Automall Bengkulu. In this study, the researcher uses data collection methods by means of observation, distributing questionnaires and interviews. There are several data analysis techniques used in this study, namely using instrument tests, classical assumption tests, analysis of respondents' responses, multiple linear regression analysis, determinant coefficients, and hypothesis testing. From the results of multiple linear regression, the regression equation is as follows: Y = 9.035 + 0.023 (X_1) + 0.435 (X2) + 0.127 (X3). The results of the t hypothesis test on the Motivation variable show tcount> ttable (2.309 > 1.98373) and sig <@ (0.008 < 0.050), the Job Satisfaction variable shows tcount> ttable (4.895 > 1.98373) and sig < @ (0.000 < 0.050), then on the variable Work stress shows tcount> ttable (2.019 > 1.98373) and sig < @ (0.046<0.050). The results of the f-test show that Fcount> Ftable (18,527 > 2,699) and sig < @ (0.000 < 0.050). So it can be concluded that motivation, job satisfaction and job stress have a positive and significant effect on employee performance at PT. Agung Automall Bengkulu.